THE EFFECT OF LIQUIDITY, PROFITABILITY, AND COMPANY SIZE ON THE TIMELINESS OF SUBMITTING FINANCIAL STATEMENTS IN MANUFACTURING COMPANIES - Wahdini, Wahdini; Ningrum, Wulan Wahyu; Jayanti, Fitri (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research aims to explain whether liquidity, profitability, and company size have a partial or simultaneous effect on the timeliness of submitting financial reports. Method: This study is quantitative in nature, using secondary data from published financial reports of manufacturing companies listed on the IDX for the 2020-2022 period. Data was obtained from the IDX website based on purposive sampling. A total of 84 companies met the criteria for inclusion, resulting in 252 samples over the three-year observation period. Logistic regression was applied to test the data at a 5 percent significance level. Results: The research results indicate that liquidity, on its own, does not influence the timeliness of financial report submissions. However, profitability and company size do have a significant effect on timeliness. Additionally, when examined simultaneously, liquidity, profitability, and company size together affect the timeliness of submitting financial reports for manufacturing companies listed on the IDX. Novelty: This study contributes to the existing literature by providing insights into the specific impact of liquidity, profitability, and company size on the timeliness of financial reporting within the manufacturing sector in Indonesia, covering a recent period from 2020 to 2022.